Additives boosting the performance of tungsten imido-mediated ethylene dimerization systems for industrial application. Issue 50 (21st May 2020) - Messinis, Antonis M.; Wright, William R. H.; Hanton, Martin J.; Dyer, Philip W.
Abstract : The [WCl2 (NAr)2 (dme)]/EtAlCl2 /( n Oct)4 NCl catalyst system is highly productive, active, and selective (>93% C4, >99% 1-C4 ) for the dimerization of ethylene to 1-butene, rivalling the performance of current commercial systems. Abstract : While activation of tungsten bis(imido) complexes [WCl2 (NAr)2 (dme)] with EtAlCl2 affords active, and moderately selective ethylene dimerization catalysts, addition of Et3 N or Oct4 NCl leads to a doubling in productivity and activity, along with increased selectivity ( e.g., >93% C4, >99% 1-C4 ). The performance of the resulting tungsten-based catalyst package is competitive with that of Axens' commercialised Ti-based AlphaButol process and exemplifies the wide potential of similar additives in selective oligomerization.